THE USE OF GOOGLE SERVICES IN MEDICAL INFORMATICS PRACTICAL CLASSES FOR STUDENTS WITH AN ADVANCED STUDY OF ENGLISH LANGUAGE - Olena Lyubchyk; Inna Kryvenko (Неперервна професійна освіта: теорія та практика)
The study highlights the methodological aspects of using Google digital tools, which contribute to a more thorough formation of practical skills in Medical Informatics in the process of teaching students with an advanced study of the English language. The advantages of using cloud technologies for better presentation of educational material while learning new knowledge are shown. The effectiveness of using Google services for the educational process organization and a high-quality method of assimilation of a large amount of information by students is substantiated using specific examples. The use of the following Google services in educational activities is described: to organize classes – Google Class; to learn English terminology, basic concepts of the topic – Google Jamboard, Google Documents; to organize control and revise of the level of knowledge formation – Google Forms; to perform video meetings – Google Meet; to master the skills of working with artificial intelligence - Gemini Google AI; Google Cloud Healthcare – for deepening medical informatics training, interdisciplinary implementation and familiarization with specialized digital services for healthcare. Together, these Google digital tools provide an opportunity to intensify the educational process, make its content more qualitative and convenient for perception and understanding, and thus contribute to better assimilation of knowledge and practical skills in Medical Informatics in comparison with traditional methods. The use of Google services in the educational process diversifies and improves the teacher's work, helps to more actively involve students in the creative processing of educational material, creates additional conditions for better understanding and assimilation of the received information.